The clonal root system of balsam poplar in upland sites of Quebec and Alberta - Adonsou, Kokouvi E.; DesRochers, Annie; Tremblay, Francine; Thomas, Barb R.; Isabel, Nathalie (Ecology and evolution, 2016)
Balsam poplar seeds are short‐lived and require moist seedbeds soon after they are released to germinate. In addition to sexual reproduction, balsam poplar stands can regenerate clonally by root suckering. The origin of stands will in turn affect their genetic structure and root system architecture, which are poorly understood for upland forest stands. Three stands were hydraulically excavated in Quebec (moist) and Alberta (dry) to determine the origin of trees and to characterize root systems with respect to presence of parental roots and root grafts connections. Clones were identified using single‐nucleotide polymorphism (SNPs), and all stems, roots and root grafts were aged using dendrochronology techniques. All 82 excavated trees were of sucker origin, and four of the six stands contained a single clone. Parental root connections were found between 22% and 25% of excavated trees, and 53% and 48% of trees were linked with a root graft between the same or different clones, in Alberta and Quebec, respectively. Mean distance between trees connected by parental root was significantly lower than the distance between unconnected trees (0.47 ± 0.25 m vs. 3.14 ± 0.15 m and 1.55 ± 0.27 m vs. 4.25 ± 0.13 m) in Alberta and in Quebec, respectively. The excavations also revealed many dead stumps with live roots, maintained through root connections with live trees. This research highlights that balsam poplar growing in upland stands is a clonal species that can maintain relatively high genotypic diversity, with frequent root connections between trees at maturity. Maintaining an extensive root system through root connections increases the chances of a clone surviving when the above ground tree is dead and may also enhance the resilience of balsam poplar stands after disturbance. Parental root connections were found between 22% and 25% of excavated balsam poplar trees, and 53% and 48% of trees were linked with a root graft between the same or different clones, in Alberta and Quebec, respectively. Mean distance between trees connected by parental root was significantly lower than the distance between unconnected trees (0.47 ± 0.25 m vs. 3.14 ± 0.15 m SE and 1.55 ± 0.27 m vs. 4.25 ± 0.13 m) in Alberta and in Quebec, respectively. The excavations also revealed many dead stumps with live roots, maintained through root connections with live trees.